Editorial - Govender, Logan; McDonald, Zahraa (Critical Studies in Teaching and Learning, 2023)
This issue and its 10 articles and four book reviews mark the 10th anniversary of CrisTal, while also commemorating Prof Michael Cross, who dedicated his academic life to building critical scholarship in teaching and learning. The 10 articles offer a comprehensive and innovative interrogation of empirical, theoretical, and epistemological concerns that the higher education sector in South Africa, and the world, are grappling with. They help draw attention to the rapidly changing edifice of the global world order, characterised by pandemics, climate change and deepening social and economic inequalities. The first five articles form part of the special issue ‘Methodological insights drawn from research focused on teaching and learning: COVID 19 and beyond’ edited by Dr Logan Govender and Dr Zahraa McDonald. These articles make a distinct contribution to methodology and / or method by foregrounding the epistemological and technical elements of methodology, drawing on fieldwork experiences during and beyond the pandemic. The remaining five articles in this issue focus on how academic staff at universities engage with the diverse range of the knowledge project in higher education: being ‘response-able’, entrepreneurial yet socially relevant, reconceptualizing Africanisation of the university, becoming an academic in a specialized discipline and usefully employing an academic literacy pedagogy. Ultimately, the articles remind us that the higher education sector, while not immune to the changing world order, has a particular role to play in shaping it, to the benefit of students, academics, and society at large. Four book reviews conclude this anniversary issue.